2018
DOI: 10.1159/000491073
|View full text |Cite
|
Sign up to set email alerts
|

F0Timing and Tone Contrasts in Luganda

Abstract: Scholars of Luganda (Bantu, Uganda) have described a contrast between falling and high tone, which is limited to syllables with a long vowel or a coda. The contrast has been represented with H on the first mora of a falling-tone syllable and on both moras in a high-tone syllable. This article explores this contrast through an instrumental study of the timing of f0 events in Luganda. It was found that the 2-tone classes differed in the timing of both the f0 rise and the subsequent f0<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
(83 reference statements)
1
6
1
Order By: Relevance
“…In Table 6, presenting the analysis of peak delay, there are significant main effects for segmental interval duration C 1 and V 1 , indicating that the f 0 rise is timed with respect to the segments of the span-initial syllable, as found previously by Myers et al (2018). When those segments are longer, peak delay is correspondingly longer.…”
Section: F 0 Timingsupporting
confidence: 67%
See 3 more Smart Citations
“…In Table 6, presenting the analysis of peak delay, there are significant main effects for segmental interval duration C 1 and V 1 , indicating that the f 0 rise is timed with respect to the segments of the span-initial syllable, as found previously by Myers et al (2018). When those segments are longer, peak delay is correspondingly longer.…”
Section: F 0 Timingsupporting
confidence: 67%
“…In this paper, we will assume for purposes of discussion that the tone-bearing unit in Luganda is the syllable, contrary to previous work that has identified the mora as the tone-bearing unit in the language (Tucker, 1962;Hyman, 1992;Hyman & Katamba, 1993;Hyman & Katamba, 2010). Myers et al (2018) found that the timing of the f 0 peak and the subsequent fall depended on the duration of the onset, the vowel of the syllable, as well as the duration of the postvocalic consonantal interval. They did not find that this dependency was sensitive to whether or not the segment was moraic, and so concluded that the mora was not relevant to the timing of f 0 events in Luganda.…”
Section: High Tone Spread In Lugandamentioning
confidence: 97%
See 2 more Smart Citations
“…There is a contrast between high and low tone in both long and short syllables, but the contrast between falling and high tone only occurs in long syllables. Both high and falling tone are characterized by a rise in f0 followed immediately by a fall, but they differ in that the f0 peak occurs earlier in the syllable in falling tone than in high tone (Myers, Namyalo & Kiriggwajjo 2019).…”
Section: Inf-growcold-fv Inf-lend-fvmentioning
confidence: 99%